THE DYNAMICS OF ACCESS REFORM ARRANGEMENT IN SALTED EGG ENTREPRENEURSHIP IN TEGAL CITY - M Nur Kamila Amrullah; Widodo Widodo; Sapardiyono Sapardiyono (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: This study aims to analyze the implementation of access reform under Agrarian Reform in promoting local entrepreneurship and improving the welfare of salted egg artisans in Pesurungan Lor Village, Tegal City. Method: This research employs a qualitative case study approach, utilizing in-depth interviews, field observations, and document analysis involving local entrepreneurs, relevant government agencies, and the Agrarian Reform Task Force. Results: The findings indicate that training, business mentoring, access to capital, and institutional strengthening have significantly enhanced the skills, productivity, and income of the entrepreneurs. Approximately 60% of beneficiaries experienced an income increase of up to IDR 3,500,000 per month. The dynamics of access reform are reflected in changes in entrepreneurial behavior, group adaptation processes, and external challenges such as market limitations and legal compliance. Novelty: These findings affirm that context-responsive access reform can serve as an effective instrument to strengthen grassroots entrepreneurship and is worth replicating in other regions with similar characteristics.